Nurses leadership evaluation by nursing aides and technicians according to the 360-degree feedback method - Eliana Ofélia Llapa-Rodriguez; Júlian Katrin Albuquerque de Oliveira; David Lopes Neto; Maria Pontes de Aguiar Campos
Objective: to assess the leadership of nurses of a maternity hospital according to the nursing aides and technicians and the 360-degree feedback method. Method: a descriptive, cross-sectional study. The population was 19 nurses and 96 nursing aides and assistants. Data were collected from May 2010 to July 2011 using a questionnaire based on the 360-degree method. Results: the nurses mentioned having a favourable performance in the four studied categories. The nursing aides and technicians disagreed with the recorded leadership performance of the nurses in the category "Communication" and "Support environment." The responses for the category "Role Model" were favourable in all items, especially PAPEL18. In "Management Style", the highest favourable rating was 79% for GESTAO16. Conclusion: the categories "Communication" and "Support Environment" revealed a greater fragility of the nurses in comparison to the categories "Role Model" and "Management Style".